THE WORLD IN MOTION IN “THE SEASONS” BY KRISTIJONAS DONELAITIS: THE CONTEXT OF ANTIQUE AND PROTESTANT PHILOSOPHY OF NATURE - POCIŪTĖ, DAINORA (Knygotyra, 2015)
In the article the famous poem “The Seasons” written in Prussia by the Lithuanian poet Kristijonas Donelaitis (1714 01 01 – 1780 02 18) is considered as a poem based on the classical tradition of the description of the seasons. In this most famous work of the Lithuanian literature one can note the principles of Aristotelian philosophy of nature. The Lutheran educational system to which Donelaitis belongs, was also to a large extent influenced by the teaching of Melanchthon who was Aristotelian. Melanchthon considered the nature studies as one of the main subjects while his aristotelism was modified according to the teaching of Christian philosophy and contained a strong element of providential optimism as well as other Protestant values. The Aristotelian and Melanchthonian philosophy of nature is the background of Donelaitis’ reflection on nature. Nevertheless, the imagery of Donelaitis’ philosophy of nature is based not on pure philosophical categories but on the observations of the daily life of Lithuanian countryside in East Prussia. Such topics as a permanent motion of the world, the sudden change from “the all” to “the nothing”, the declination of life are the dominating tendencies of the reflection on nature in “The Seasons”by Donelaitis. Anyway, the Lithuanian poet does not suggest that the radical human responses to nature’s instability (i. g. weeping of Heraclitus or the laughing of Democritus) are proper to the pious and modest Christian life.
Keywords: ...